Towards a Better Understanding of Sickness Absence in Adolescence: A Qualitative Study among Dutch Intermediate Vocational Education Students. (9th May 2017) - Vanneste, Yvonne T. M.; Feron, Frans J. M.; van Mook, Marlieke A. W.; de Rijk, Angelique
Abstract : An adequate approach to sickness absence can reduce school dropout which is a major problem in Intermediate Vocational Education (IVE). This practice-based study explores the sickness absence reasons and factors influencing reporting the sickness, from a student's perspective. Semistructured interviews were held until saturation. Data were collected and analysed by a multidisciplinary research team including youth health care physicians working with IVE students. The results show that, according to the students, reasons for sickness reporting were health-related or related to problems at home or in school. Students view their sickness absence as necessity, as asking for understanding, or as pardonable. Their views depended on (1) the perception of medical legitimacy, (2) feeling able to take their own responsibility, (3) feeling being taken seriously at school, and (4) the perception that the sickness reporting procedure at school is anonymous and easy. In conclusion, reporting sickness seems more a reaction to a necessity or opportunity than the result of a conscious decision-making process. Personalizing the sickness reporting procedures and demonstrating interest rather than control while discussing the sickness absence with the individual IVE student might very well affect their sickness absence levels.